Double pituitary adenomas: report of two cases and systematic review of the literature - Zhang, Yi; Gong, Xinyue; Pu, Jun; Liu, Jifang; Ye, Zhang; Zhu, Huijuan; Lu, Lin; Pan, Hui; Deng, Kan; Yao, Yong (Frontiers in Endocrinology, 2024)
Objective Double pituitary adenomas (DPA) are a rare clinical condition, and our knowledge of them is limited. Missing the second lesion leading to incomplete biochemical remission after surgery is an important challenge in DPA management. This study aims to analyze independent prognostic factors in DPA patients and summarize clinical experiences to prevent surgical failure. Methods Two cases of DPA patients with Cushing’s disease diagnosed and surgically treated at Peking Union Medical College Hospital are reported. A literature review was performed on the online database Pubmed, and 57 DPA patients from 22 retrieved articles were included. Demographic characteristics, endocrine manifestations, diagnostic methods, tumor size, and immunohistochemical features of 59 patients were analyzed. Binary logistic regression models were used to identify independent prognostic factors affecting postoperative biochemical remission. Results Among 59 DPA patients, the mean ± SD age was 43.64 ± 14.42 years, with 61.02% being female (n = 36). The most common endocrine manifestations were Cushing’s syndrome (23/59, 38.98%) and acromegaly (20/59, 33.90%). The most prevalent immunohistochemical types were ACTH-immunopositive (31/118, 26.27%) and GH-immunopositive (31/118, 26.27%) tumors. Microadenomas (<1cm) were the most frequent in terms of tumor size (62/92, 67.39%). The detection rate for double lesions on 3.0T MRI was 50.00% (14/28), which significantly higher than 1.5T MRI (P = 0.034). Univariate analysis revealed that female, Cushing’s syndrome and only single lesion detected by surgical exploration were associated with significantly worse prognosis (P<0.05). Multivariate analysis identified double lesion detected by surgical exploration (OR = 0.08, P = 0.003) and contiguous type tumor (OR = 0.06, P = 0.017) as independent protective factors for DPA patients. Conclusions The double lesion detected by surgical exploration is independently associated with a better prognosis for DPA patients. Comprehensive intraoperative exploration are crucial measures to avoid missing causative lesions.